The popular proverb between depicting experience and the frameworks of criticism - Assi, Omar Mahmoud (Journal of Arabic Language Sciences and Literature, 2024)
This research focuses on studying the various contextual factors that contribute to the formation of proverbs, with the unconscious mind being at the forefront, encompassing all aspects of psychological life. Therefore, studying the unconscious enables us to interpret all psychological phenomena that constitute a significant part of the proverbs. A proverb does not merely reflect the social experience that encapsulates an engaging folk story; rather, it harbors a deep psychological system shaped by the unconscious mind emerging from various contextual factors. The proverb expresses psychological truths and natures, and its value lies in its expression of the latent aspects of the psyche that society is unaware of. This requires addressing concepts related to the study, the most prominent of which are: the folk proverb, individual unconscious, collective unconscious. It also examines the process of folk proverbs and the methods of their transmission and preservation, utilizing the descriptive-analytical method alongside the psychological method. The research includes some practical examples by referring to some Palestinian folk proverbs. It is organized into three sections, preceded by an introduction. The first section focuses on defining the most important terms related to the study, while the second gives special attention to the unconscious to clarify its impact on shaping the content of proverbs and imposing them on consciousness. The third section examines the evolution of folk proverbs and the methods of their transmission and preservation. These sections are concluded with a conclusion that summarizes the most important findings and recommendations reached.
Keywords: proverb; culture; unconscious; subconscious